THE ROLE OF TRAINING AND DEVELOPMENT IN IMPROVING EMPLOYEE PERFORMANCE: A REVIEW OF HRM LITERATURE - Johni Eka Putra; Tehedi Tehedi (INJOSEDU: International Journal of Social and Education, 2025)
This article examines the role of training and development in improving employee performance through a review of Human Resource Management (HRM) literature. The method used in this study uses the literature method. The results of the review show that structured and relevant training programmes can improve employees' skills, knowledge and motivation, which in turn have a positive impact on individual productivity and organisational performance. In addition, continuous development helps employees to stay relevant to the latest industry and technological developments, which enhances organisational adaptability and competitiveness. Factors such as management support, an organisational culture that supports learning, and access to diverse learning opportunities were found to play an important role in the success of training programmes. Overall, training and development is an essential strategic investment for the long-term development of employees and organisations, and building sustainable competitive advantage.